LGMD D2 TNPO3-Related: From Clinical Spectrum to Pathogenetic Mechanism - Costa, Roberta; Rodia, Maria Teresa; Pacilio, Serafina; Angelini, Corrado; Cenacchi, Giovanna (Frontiers in Neurology, 2022)
Limb-girdle muscular dystrophies (LGMDs) are clinically and genetically heterogeneous diseases presenting with a wide clinical spectrum. Autosomal dominant LGMDs represent about 10-15% of LGMDs and include disorders due to defect of DNAJB6, Transportin-3 (TNPO3), HNRNPDL, Calpain-3 (CAPN3), Bethelem myopathy. The aim of this review article is to describe the clinical spectrum of LGMD D2 TNPO3-related, a rare disease due to heterozygous mutation in TNPO3 gene. TNPO3 encodes for Transportin-3, which belongs to the importin beta family and transports into the nucleus serine/arginine-rich (SR) proteins, such as splicing factors, and HIV-1 proteins, thus contributing to viral infection. The purpose of this review is to present and compare the clinical features as well as the genetic and histopathological findings described in LGMD D2, performing a comparative analytical description of all the families and sporadic cases identified. Even if the causative gene and mutations of this disease have been identified, the pathogenic mechanisms are still open issue, therefore we will present an overview of the hypotheses that explain the pathology of LGMD D2 TNPO3-related.